Optimizing Quality Assurance in Breast IMRT Treatment Plans: A Comparative Study of Point Dose and 2D Dose Verification - Herwiningsih, S.; Noor, J. A. E.; Widodo, C. S.; Munthe, D. Y. B.; Hentihu, F. K. (National Research and Innovation Agency, 2025)
Intensity-Modulated Radiation Therapy (IMRT) requires rigorous dose verification to ensure accurate radiation delivery. This study evaluates point dose verification and 2D dose verification techniques in detecting dose discrepancies due to isocenter shifts in IMRT treatment for post-mastectomy breast cancer cases. Five post-mastectomy breast IMRT plans were retrospectively analyzed, with phantom-based measurements compared against Treatment Planning System (TPS) calculations. The results indicate that point dose verification provides reliable absolute dose measurements, but lacks spatial resolution, whereas 2D verification captures dose variations more effectively. Dose discrepancies remained within acceptable limits for shifts up to ±3 mm, but shifts of ±5 mm or more resulted in clinically significant deviations. Gamma Passing Rates (GPR) decreased substantially beyond ±5 mm shifts, underscoring the importance of precise patient positioning. These findings support the integration of both verification methods to improve IMRT quality assurance, particularly in resource-limited settings. Future advancements in AI-driven dosimetry and real-time in vivo monitoring may further optimize dose verification, enhancing treatment accuracy and patient safety.